Vigorous New Particle Formation Above Polluted Boundary Layer in the North China Plain. Issue 22 (15th November 2022) - Lai, Shiyi; Huang, Xin; Qi, Ximeng; Chen, Liangduo; Ren, Chuanhua; Wang, Zilin; Wang, Jinbo; Lou, Sijia; Chi, Xuguang; Gao, Yang; Hai, Shangfei; Petäjä, Tuukka; et al.
Abstract: Atmospheric new particle formation (NPF) is vital in climate and air pollution for its contribution to aerosols and cloud condensation nuclei; however, a vertical understanding of NPF is still limited. Here, simultaneous observations at two altitudes were conducted over the North China Plain. Despite a high aerosol loading during cold season, NPF is still frequently observed. The upper‐air NPF is increasingly intensive and starts earlier as haze pollution deteriorated, and the onset time gap could exceed 3 hr. To understand the factors modulating NPF vertically, we updated the meteorology‐chemistry model by incorporating state‐of‐the‐art nucleation schemes and performed highly vertical‐resolved simulations. It is revealed that vertical disparities in NPF are attributed to the pronounced stratification of sulfur dioxide, ozone, and particulate matter. As the evolution of the boundary layer, strong NPF in the upper air elevates the near‐surface nucleation‐mode particles. This work sheds more light on the vertical structure of NPF. Plain Language Summary: New particle formation (NPF) is a worldwide phenomenon and is regarded as a major contributor to the global cloud condensation nuclei (CCN) as well as to air pollution. Given the vertically varied cloud distribution and the vital role of NPF in CCN, it is of great importance to understand the vertical structure of NPF. However, the overwhelming majority of NPF studies are based on near‐surface measurements. By conducting simultaneous observations at two different altitudes in the polluted North China Plain, our study demonstrated that there is an earlier and stronger NPF event in the upper air, especially on polluted days. It is revealed that vertical disparities in NPF are mainly attributed to the pronounced stratification of sulfur dioxide, ozone and particulate matter concentrations in the planetary boundary layer. The differences in NPF onset time together with formation and growth rate in vertical suggest potentially significant impacts on low clouds and particle pollution near the ground. This work shed new light on the vertical structure of NPF and thus their effects on climate change and air pollution. Key Points: Vigorous new particle formation (NPF) above polluted boundary layer was observed over the North China Plain Vertical heterogeneities in precursors, oxidizing capacity, and condensation sink favor the NPF in the upper air NPF in upper boundary layer has a decisive impact on near‐surface aerosol number and cloud condensation nuclei